IMPLMENTASI PENDIDIKAN AGAMA ISLAM MELALUI BUDAYA RELIGIUS (RELIGIOUS CULTURE) DI SEKOLAH - Kristiya Septian Putra (Institut Agama Islam Negeri Purwokerto, 2017)
The education system of Islamic Religion in school is a form of elaboration of the mandate of Act No. 20 of 2003 on National Education System, in order to prepare students to be a man of faith and piety and morality, but in practice they have drawn criticism from the public that PAI in school during is rated only equip learners only religious knowledge (cognitive) less emphasis on the aspect of practice (affective and psychomotor). Where necessary the development of PAI itself, so that PAI is not only limited knowledge but also can be practiced in everyday life either at school or in everyday environments. Either by teachers, and students.Therefore, it is necessary to build a culture of religious (religious culture) in religious activities in schools to improve the practice of affective so in tune with our educational goals.